El cambio de una auditoria tradicional a una auditoria basada en riesgos (2023)
Companies will always be exposed to the risks that are accepted, in order to generate great value to it, for this reason it is of great importance that they have an internal control system that is in charge of risks, that helps them control and minimize these. Internal control is based on an Audit at the time of its proper functioning of the different processes of a company, since it is in charge of overseeing and monitoring that everything is carried out and fulfilled in an adequate manner.